From luminescence quenching to high-efficiency phosphorescence: a theoretical study on the monomeric and dimeric forms of platinum(ii) complexes with both 2-pyridylimidazol-2-ylidene and bipyrazolate chelates. Issue 9 (3rd March 2021) - Zhang, Bo-Hua; Li, Jun-An; Wang, Min; Ren, Ai-Min; He, Teng-Fei; Lin, Pan-Pan; Zhang, Yun-Li; Xi, Xiao-Yue; Zou, Lu-Yi
Abstract : To develop solid-state light-emitting materials with high luminescence efficiency, determining the potential photophysics and luminescence mechanisms of the aggregation state remains a challenge and a priority. Abstract : To develop solid-state light-emitting materials with high luminescence efficiency, determining the potential photophysics and luminescence mechanisms of the aggregation state remains a challenge and a priority. Here, we apply density functional theory to study the photophysical properties of a series of square planar Pt(ii ) complexes in both monomeric and dimeric forms. We reveal that four monomeric Pt(ii ) complexes are dominated by triplet ligand-to-ligand charge-transfer, and the lack of the triplet metal-to-ligand charge-transfer feature results in weak spin–orbit coupling (SOC), which leads to limited radiative rates; moreover, calculated nonradiative transition rates are one or two orders of magnitude higher than those radiative rates because a large amount of reorganization energy caused by the vibration of the bipyrazolate (bipz) ligand cannot be readily suppressed in the monomeric form. Therefore, four monomers exhibit photoluminescence quenching in CH2 Cl2 solution in both theoretical calculations and experiments. However, in the solid state, the intense luminescence phenomenon indicates obviously distinct properties between the monomer and aggregation. We carried out a dimer model to interpret that the interaction of Pt⋯Pt induces a metal–metal-to-ligand charge-transfer excimeric state, which leads more metal components to participate in the charge transfer and enhance the SOC effect. At the same time, the ligand vibration can be significantly reduced by the shortened distance, and there is a strong π–π packing interaction in the dimer; thus, an excellent quantum yield can be achieved in aggregation. In addition, we disclose that introducing bulky substituents bearing electron-donating groups at R′ and R′′ positions have little effect on the properties of the monomers; however, there is a benefit of restricting the internal reorganization energy through the intermolecular interaction when packing in the solid state. Therefore, substitutions can be tuned to improve the properties of monomers (such as emission energy and reorganization energy). We hope that our work will shine some light on Pt(ii ) emitters in the fabrication of efficient OLEDs.